An analytical framework for science parks and technology districts with an application to Singapore - Koh, Francis C.C.; Koh, Winston T.H.; Tschang, Feichin Ted (Journal of Business Venturing, 2005)
This paper analyzes the question: What does it take for science parks and technology districts to evolve and grow? We propose an analytical framework to examine the gestation, evolution, and sustainability of science parks and related but broader regional phenomena such as technology districts. The framework comprises three aspects of a science park's development: growth mechanisms, level of technological capabilities, and nature of its integration with national or global markets. The main growth mechanisms we identify are government-led infrastructure provision, agglomeration effects, and continual self-renewal through the creation of new businesses. We apply this framework to analyze Singapore's science park strategy and the recent One-North initiative.